Essays in Anthropology and Semiotics of Folklore - Emilija Mijić (University of Belgrade, 2016)
Review of the book by Dragana Antonijević. Essays in Anthropology and Semiotics of Folklore. 2010. Beograd: Srpski genealoški centar i Odeljenje za etnologiju i antropologiju Filozofskog fakulteta, 257 pp.